Genetic polymorphism of ADAM17 and decreased bilirubin levels are associated with allergic march in the Korean population - Jaemee Jung; Dahyun Hwang (BMC, 2022)
Abstract Background The "allergic march" refers to changes in the frequency and intensity of allergic diseases with age. Classically, the allergic march begins with atopic dermatitis in infancy and leads to asthma and rhinitis as it continues. There are many factors that induce the allergic march; however, TNF-α may play an important role in inducing inflammation. Therefore, the therapeutic potential of TNF alpha-targeting agents is being considered for allergic march treatment. Methods We performed a correlation study to determine whether genetic polymorphisms of ADAM17 and clinical serum values between allergic and normal groups affect disease development by using the cohort data of the Korean genome epidemiologic research project. Gene association study was performed using PLINK version 1.07 ( http://pngu.mgh.harvard.edu/-purcell/plink ) and other statistical analysis was performed using PASW Statistics (version 18.0, SPSS Inc. Chicago, IL, USA). Results ADAM17 (also called TNF-α converting enzyme or TACE) showed a statistically significant association with the allergic march. The 13 and 8 SNPs in ADAM17 were significantly associated with asthma and allergies, respectively. Among them, on average, SNP of rs6432011 showed the greatest statistical correlation with asthma (P = 0.00041, OR = 1.95, 95% CI 1.35-2.82) and allergies (P = 0.02918, OR = 1.35, 95% CI 1.03-1.78). The effect of SNPs in ADAM17 on transcription factor binding was confirmed using RegulomeDB. The six SNPs are located in the genomic expression quantitative trait loci (eQTL) region and can affect transcription factor binding and gene expression. In clinical serum analysis, bilirubin levels were significantly decreased in the allergic group. The multivariate logistic regression analysis revealed that the low-bilirubin groups indicated a 3.22-fold increase in the prevalence of asthma compared with the high-bilirubin group. Conclusions The ADAM17 gene and low bilirubin levels are associated with the allergic march in the Korean population, which can provide new guidelines for managing this disease progression phenomena.